1999
DOI: 10.1007/bf03257237
|View full text |Cite
|
Sign up to set email alerts
|

A noninvasive method of measuring wave intensity, a new hemodynamic index: application to the carotid artery in patients with mitral regurgitation before and after surgery

Abstract: Wave intensity (WI) is a new hemodynamic index, which is defined as (dP/dt)(dU/dt) at any site of the circulation, where dP/dt and dU/dt are the time derivatives of blood pressure and velocity, respectively. Arterial WI in normal subjects has two positive sharp peaks. The first peak occurs during early systole when a forward-traveling compression wave is generated by the left ventricle. The magnitude of this peak increases markedly with an increase in cardiac contractility. The second peak, which occurs toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 17 publications
5
45
0
Order By: Relevance
“…A close relation between the first peak of aortic WI and LV max. dP/dt was found in dogs [14], and the same relation was predicted from theoretical considerations [21,32]. Here, clinical measurements have confirmed a similar relation between carotid arterial WI and LV max.…”
Section: Ultrasonic Measurements Of Wave Intensitysupporting
confidence: 88%
See 3 more Smart Citations
“…A close relation between the first peak of aortic WI and LV max. dP/dt was found in dogs [14], and the same relation was predicted from theoretical considerations [21,32]. Here, clinical measurements have confirmed a similar relation between carotid arterial WI and LV max.…”
Section: Ultrasonic Measurements Of Wave Intensitysupporting
confidence: 88%
“…They performed animal experiments and found that the height of the first positive peak of aortic wave intensity, which appeared early in systole and coincided with rising pressure and acceleration, increased with an increase in cardiac contractility. This relation was also derived theoretically [21,32].…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…The original formulation required invasive simultaneous measurements of blood pressure and flow velocity (U), but the parallel development of ultrasound systems enabled performing WIA through ultrasound-measured diameter (D) and U instead [3,4]. D and U are commonly filtered (smoothed) to eliminate high-frequency noise; however the filter settings affect WIA parameters, calculated not directly from D and U, but from their time derivatives (dD, dU) [5].…”
Section: Introductionmentioning
confidence: 99%